Mendorong Inovasi di Pemerintah: Hambatan dan Strategi - Heru Syah Putra (Puslatbang KHAN, 2017)
Innovation becomes a need in public service organizations. It enables the government to deliver more effective and efficient services. However, the development of innovation in government organization may encounter barriers. This study aims to identify the common barriers that hamper the development of innovation in government, especially in public service institutions. This study reviews academic articles that explore the problems and strategies in fostering innovation. The result shows that innovation encounter at least thirteen barriers both in the early stage and advanced stage of innovation development. The most common problems are weak leadership, the gap of understanding, and resistant culture. Leaders who are lack of innovation experience unable to motivate others to innovate. Further, the gap of understanding among worker may lead to lack of support on a certain innovation. An organization that resistance to change encounter difficulty to innovate. Thus, there are four steps that can be taken to push innovation in government; generating possibilities, incubating and prototyping, replication and scaling up, and analyzing and learning.